Medicinal and Aromatic Plants Value Chain Performance in Albania: Information System Implementation (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2018)
The medicinal and aromatic plants (MAPs) represent a very important sector for the Albanian economy. According the COMTRADE 2018 statistics, this sector exports rank the country at the 16-th position in the World, indicating that Albania has a very big economical potential in this area (Hoxha, 2016, Naka et al., 2003). Despite this potential, the last 20 years records show that these exports have remained almost constant. The lack of information about the value chain, indicating the asymmetric information is the main reasons of this performance (USAID, 2010, Lekocaj et al, 2017). Therefore, conclusion emerges that there is a limited rationality between the economic agents who work and study in this sector. This study object is to identify the information sources and to fabricate all the channels where this information goes through. To achieve our objectives, we are using systemic approach. At the national level, we have chosen 3 municipalities, while for the information level regarding this sector’s actors we have chosen 12 exporting companies, the most important ones in Albania. The results show that the sector information system has methodological problems on their identification and a lack of a central database, which can be updated at any moment with new information in time and space from all the value chain actors.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.